Application Of Accounting System on Account Payments: Study At One of The Hotels in Bandung - Karmila, Karmila; Nasution, Sakti Muda; Fudsy, Mira Ismirani; Karmana, Dedi; Lesmana, Budi (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study seeks to elucidate the process of executing debt payments at Dejava Hotel Bandung and to identify the obstacles impeding these payments. This research constitutes a form of qualitative descriptive investigation. To perform this study, the author seeks primary data through direct interviews with relevant parties and secondary data in financial reports and supplementary documents. The study's findings at De Java Hotel indicate that the execution of debt payments to suppliers occurs through two interconnected processes: the purchase report method and the debt payment procedure. The issues impeding the settlement of trade debts to suppliers include the late arrival of invoices and the untimely submission of warehouse reports, leading to delayed payments. To ensure timely debt payments, the organization frequently needs to request clear invoices from the supplier and enhance warehouse monitoring.